2013
DOI: 10.1111/j.1365-2125.2012.04373.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of peginterferon alfa‐2a (40KD) on cytochrome P450 isoenzyme activity

Abstract: AIMPegylated interferon-based therapy is recommended for treatment of hepatitis C virus (HCV) infection. Because interferons are known to down-regulate hepatic cytochrome P450 (CYP) enzymes, which are involved in drug metabolism and clearance, there is a need to investigate the effect of peginterferon (PEG-IFN) alfa-2a (40KD) on the activity of these enzymes in vivo. METHODSFourteen healthy, male volunteers aged 18 to 45 years were recruited into an open label, two period, single centre study in which CYP enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Since suppression of CYP3A4 gene expression in inflammatory diseases can lead to improper drug metabolism and poor efficacy of therapeutic drugs, it is important to determine the effects of new therapies on CYP3A4 and other DME genes. Notably, biological therapies which target specific interferons (Pegasys; peginterferon α-2a) and the therapeutic monoclonal antibody targeting IL-6 receptor (tocilizumab), could de-repress the CYP3A34, CYP2C9, and CYP2C19 enzymes in vitro and in clinical studies [ 48 , 49 ] . Other biological therapies such as TNF-α antagonists did not suppress these CYP450 genes, but were reported to increase the risk of infections and other skin diseases [ 50 ].Therefore, conventional therapies (glucocorticoid therapy, vitamin D analogs) for psoriasis will continue to remain clinically relevant.…”
Section: Resultsmentioning
confidence: 99%
“…Since suppression of CYP3A4 gene expression in inflammatory diseases can lead to improper drug metabolism and poor efficacy of therapeutic drugs, it is important to determine the effects of new therapies on CYP3A4 and other DME genes. Notably, biological therapies which target specific interferons (Pegasys; peginterferon α-2a) and the therapeutic monoclonal antibody targeting IL-6 receptor (tocilizumab), could de-repress the CYP3A34, CYP2C9, and CYP2C19 enzymes in vitro and in clinical studies [ 48 , 49 ] . Other biological therapies such as TNF-α antagonists did not suppress these CYP450 genes, but were reported to increase the risk of infections and other skin diseases [ 50 ].Therefore, conventional therapies (glucocorticoid therapy, vitamin D analogs) for psoriasis will continue to remain clinically relevant.…”
Section: Resultsmentioning
confidence: 99%
“…However, there had been reports of PEG-interferon a-2b inhibiting CYP1A2, albeit very mildly. These studies had assessed the effect of PEG-interferon a-2b after approximately 1 month of treatment (Gupta et al, 2011;Brennan et al, 2013), which is much longer than the duration reported for our study. Further, in a parallel arm to our study, PEG-interferon a-2b and ribavirin were administered in an identical regimen in combination with faldaprevir and had no effect on CYP1A2 and CYP2C9 activities .…”
Section: Introductionmentioning
confidence: 89%
“…Presently, PEGylated interferons, made by addition of poly-ethylene glycol side chain to the interferon, are being used in combination therapies for diseases such as hepatitis B and hepatitis C. As mentioned in the Table. 2, clinically significant drug interaction studies with PEGylated interferons have not been carried out to a large extent, however, studies have shown that its treatment was associated with increase in AUC of theophylline [27] and methadone [16]. …”
Section: Biologics-small Molecule Drug Interactionsmentioning
confidence: 99%
“…Likewise, in healthy volunteers, PEG-IFN alfa-2a increased the AUC 0-∞ of theophylline that paralleled with reduction in its clearance [27]. In vitro , interferon-α was found to down-regulate CYP1A2 gene, which probably explains the decreased theophylline clearance by interferon.…”
Section: Regulation Of Drug Metabolizing Enzymes During Inflammatimentioning
confidence: 99%